From Care to Education in the Spanish Nurseries for Children Aged 0 to 3 Years (1990–2020). - Sanchidrián-Blanco, María del Carmen (CLUEB, 2022)
This chapter looks into the evolution of day nurseries and educational services for children aged zero to three years in Spain from 1945 to 1990, and how they compare with those for children aged three to six. The main reforms, actors and legislation will be analysed. At least two different periods may be identified: from 1945 to the breakdown of fascism in 1975, and from then to 1990. The three most important educational laws were the Ley de 17 de Julio de 1945 sobre Educación Primaria, dividing preschool education into maternales and escuelas de párvulos that remained the first level of primary school); the Ley 1970 Law of education, introducing important changes to the education system (preschool was considered the first level of the education system and it was divided into two stages: jardín de infancia for two- and three-year-olds, and escuelas de párvulos for those aged four and five years); and the National Organic Law of Education (Ley de Ordenación General del Sistema Educativo, or LOGSE), introduced in 1990, that, for the first time, introduced two age groups: four months to three years, and three to six years. As a result, there was spectacular progress in ECEC for children aged three and over, while ECEC for children under three saw rather meagre development. Spain is an example of a country developing early childhood facilities in the context of the education system: care for children under three is not administered by welfare, but by educational authorities. This model causes difficulties for families since the characteristics of the preschool model (long holidays, rigid hours, large classes and so on) do not always satisfy the needs of either working parents or children
Opera pubblicata in modalità Open Access con licenza Creative Commons Attribuzione 4.0 (CC BY)
Keywords: Enseñanza preescolar - España; Guarderías; Early Childhood Education; Spain; Early Childhood Education and Care; 0 to 3